Role of lidocaine and its effect on postoperative outcomes in abdominal cholecystectomy - Afzal, Ayesha; Akabar Waheed Syed; Qaisar Mansoor; Rashida Farooqi; Kulsoom Farhat; Ammara Khan; Iffat Ara (Journal of the Pakistan Medical Association, 2022)
Objectives: To investigate the role of pre- and intra-operative lidocaine infusion on post-operative pain management. Method: The interventional, prospective study was conducted from September 2019 to June 2020 at the Pakistan Ordnance Factories Hospital, Wah Cantt, Pakistan, and comprised patients aged 18-60 years undergoing elective cholecystectomy who were randomised into intervention group A and control group B. Group A was given a bolus dose of lidocaine hydrochloride 2 mg/kg in addition to the standard anaesthesia protocol, while group B was given continuous intravenous infusion of 0.9% normal saline along with the standard protocol. Blood samples for interleukins 6 and 8 were taken at baseline, and then at 2, 6 and 8 hours Post-operatively. Data was analysed using SPSS 23. Results: Of the 40 patients, 20(50%) were in each of the two groups. There was a marked decrease in interleukins 6 and 8 levels group A compared to group B (p<0.05). Interleukin 8 level showed a marked decline compared to that of interleukin 6 (p<0.05). Conclusion: A decrease in interleukins 6 and 8 levels highlighted the anti-inflammatory role of lidocaine and resulted in a decrease in post-operative opioid consumption. Key Words: Anaesthetic adjuvants, IL-6, IL-8, Opioid-free analgesia, Lidocaine.